Abnormal platelet count as a prognostic indicator in community-acquired pneumonia in children - Aditi Baruah; Nibedita Paul (Indian Journal of Child Health, 2021)
Background: Platelets play an important role in the host defense mechanism during bacterial infection, besides their hemostatic action. Objective: The objective of the study was to find out whether abnormal platelet count can be used as a prognostic indicator for the severity of community-acquired pneumonia (CAP) in children by determining the relationship of abnormal platelet count (high/low) with complications of pneumonia. Materials and Methods: An observational study was conducted with a total of 298 children of ages 2 months–5 years admitted with a complaint of pneumonia, between June 2015 and May 2016 into a tertiary care teaching hospital. Complications of pneumonia were identified. Platelet count, total leukocyte count (TLC), and C-reactive protein (CRP) were estimated. Time taken for recovery was calculated. Relationship of platelet count with different types of complications, time taken for recovery, TLC, and CRP were analyzed. Results: The male to female ratio was 1.6:1 and 85.9% of children belonged to 2–12 months of age. Complications of pneumonia were empyema (7.4%), septicemia/meningitis (11.4%), and shock (14.8%). Platelet count was normal in 68.1%, high in 8.05%, and low in 23.8% of cases. There was a significant relationship between abnormal platelet count and complications (p